Comparing the Antibacterial Efficacy of Nanosilver vs Traditional Fluoride Varnishes in Caries Prevention - Jagriti Kushwah; Akshata Ron; Sanjana Khullar; Sushma Singh; Kasthuripriya Kuppusamy; Prateek J. Pachore (Journal of Pharmacy and Bioallied Sciences)
Background: Dental caries remains a prevalent chronic condition affecting individuals worldwide, particularly children. Traditional fluoride varnishes have long been employed in caries prevention due to their ability to enhance enamel remineralization and reduce demineralization. Materials and Methods: A randomized controlled trial was conducted involving 120 participants aged 6–12 years with a high risk of dental caries. The participants were divided into two groups: one receiving nanosilver varnish and the other receiving traditional fluoride varnish. Each varnish was applied bi-weekly for six months. Salivary samples were collected at baseline, three months, and six months to measure bacterial counts, focusing on Streptococcus mutans. The data were analyzed using ANOVA to assess differences between the groups over time. Results: At baseline, both groups exhibited similar levels of Streptococcus mutans (P > 0.05). After three months, the nanosilver group showed a significant reduction in bacterial counts (mean reduction of 45%, P < 0.01), compared to a 30% reduction in the fluoride varnish group (P < 0.05). At six months, the nanosilver group maintained a 55% reduction, whereas the fluoride group showed a 40% reduction. The difference between the groups at six months was statistically significant (P < 0.01). Conclusion: Nanosilver varnish demonstrated superior antibacterial efficacy compared to traditional fluoride varnish in reducing Streptococcus mutans levels over six months. These findings suggest that nanosilver could serve as a valuable alternative or adjunct to fluoride varnish in caries prevention strategies.